Digital Marketing Strategy to Increase Promotion and Sales of Banana Stem Craftsmen in Kedungkeris Village - Sari, Niken Permata; Mindhayani, Iva (Edumedia Solution, 2025)
Through a digital marketing strategy, this community service activity focuses on optimizing the promotion and sales of banana stem craft products in Kedungkeris Village, Nglipar, Yogyakarta. The background of this program is based on the potential of unique crafts from banana stems, such as mini photo frames, baskets, flip-flops, songkok, sling bags, and pencil cases, as local MSME products with high value. However, these products still have limited market reach and promotion due to a minimal understanding of utilizing digital platforms. The shift in consumer behavior towards the courage to shop post-pandemic also further emphasizes the importance of a digital presence for their business desires. The main objective of this service is to improve the craftsmen's understanding and digital marketing skills. The activity was carried out at the Kedungkeris Village Hall and involved 26 participants who were banana stem craftsmen. The material provided includes the basics of digital marketing, utilization of social media (especially Instagram and Facebook), e-commerce strategies (Shopee and Tokopedia), and practical tips for optimizing promotion and sales. The approach used is interactive lectures and discussions, helping participants understand essential concepts such as determining target markets, product innovation (including combining crafts with culinary products as hampers), and ease of access to purchases through digital channels. The implications of this activity are expected to increase the capacity of digital craftsmen significantly, expand the market reach of Kedungkeris banana stem products, and ultimately increase sales turnover and the economic welfare of the local community sustainably.